Strategi Pendidikan Agama Islam dalam Meningkatkan Kualitas Kepribadian Siswa di MTs Negeri Probolinggo - Hamid, Abdul (At- Ta'lim : Jurnal Pendidikan, 2018)
Education has always sought to provide guidance to students to establish and develop science and personality intact. The importance of improving the quality of education for students, and based on the term that education is as one program that can prepare and predict the development of students in the future, then, some efforts should be made by the Islamic educational institutions. In this case, MTs Probolinggo is one that should be oriented to achieve the quality of personality to development and prepare future generations who are ready to face the globalization era. In achieving this goal, the Islamic religious education in particular must have the correct strategy and precise in its development.Based on the reality happened in MTs Probolinggo, the learning of Islamic religious education in schools had been running in precise. But Islamic religious education especially MTs Probolinggo this should be taken to ensure that students not only can learn by heart religious lessons, but also able to be affective and behavioral. It is evident that in the previous year students MTs Probolinggo one has a moral decline that is one of the students exposed to cases of liquor. But it can be solved by getting serious handlers by the school so that the good name of MTs Probolinggo back brilliantly.From the background of the above problems, the researcher is motivated to conduct the research on the strategy of Islamic religious education in improving students' personalities in MTs Probolinggo. The focal points of this study are: (1) how is the steps of learning Islamic religious education in improving the quality of students' personalities in MTs Probolinggo?; (2) how is the implementation of learning Islamic religious education in students personality development in MTs Probolinggo?.The objectives in this study are: (1) to describe the steps of learning Islamic religious education in improving the quality of students' personalities in MTs Probolinggo; (2) to describe the implementation of learning Islamic education in improving the quality of students' personalities in MTs Probolinggo.Based on the data obtained and the result of this research, it can be can be summarized as follows: The first steps of learning Islamic education in improving the quality of students' personalities in the MTs Probolinggo can be quite good. Teachers of Islamic religious education in MTs Probolinggo has taken steps learning through teacher's council of Islamic religious education lessons, ranging from the preparation of the appropriate standard of syllabus content, standard competence and guide the preparation curriculum KTSP; make analysis today effective; effective last analysis; annual program; term program and lesson plan. Keywords: Islamic education strategy, Improving the quality of student personality